(untitled) (Research, Society and Development, 2025)
Introduction: Acute cardiogenic pulmonary edema (ACPE) is a medical emergency characterized by rapid accumulation of fluid in the lungs, secondary to increased pulmonary capillary wedge pressure due to cardiac dysfunction. Left ventricular failure is the main cause, resulting in severe respiratory impairment that requires immediate intervention. Objective: The present study aims to review the pathophysiology, diagnosis, and therapeutic strategies of ACPE, with emphasis on the emergency approach. Methodology: An integrative literature review was carried out in indexed databases such as PubMed MEDLINE, SCIELO, Ebscohost, Google Scholar, and the Virtual Health Library (VHL), using the descriptors “Acute cardiogenic pulmonary edema”, “Heart failure,” and “Treatment”. Articles published between 2010 and 2024 were selected, prioritizing clinical studies, systematic reviews, and international guidelines, with data critically analyzed, focusing on clinical presentation, diagnosis, and therapeutic strategies. Results and Discussion: The review showed that the diagnosis of EAPC is based on clinical criteria — such as sudden dyspnea, pulmonary rales, and orthopnea — associated with radiological findings of bilateral alveolar infiltrate. Treatment involves ventilatory support, loop diuretics, vasodilators, and, in refractory cases, the use of inotropes. New evidence points to the role of early noninvasive ventilation as a factor in reducing mortality. Conclusion: EAPC remains a therapeutic challenge, requiring immediate diagnosis and early intervention to improve survival.